Freedom and the construction of Europe - Skinner, Quentin (Cambridge Univ. Press, 2013)
v. 1. Religious and constitutional liberties -- v. 2 Free persons and free states
Keywords: Aufsatzsammlung; Konferenzschrift; Geschichte; Verfassung; Bürger; Freiheit; Religionsphilosophie; Europa